Oscillatory fluid flow enhanced mineralization of human dental pulp cells - Yortchan, Witsanu; Puwanun, Sasima (Frontiers in Bioengineering and Biotechnology, 2025)
The purpose of this study is to evaluate the optimum frequency of oscillatory fluid flow (OFF) for increasing osteogenesis in human dental pulp cells (DPCs) in an incubating rocking shaker. DPCs from 3 donors were cultured in an osteogenic induction medium (OIM) and mechanical stimulation was applied using an incubating rocking shaker at frequencies of 0 (control), 10, 20, 30, and 40 round per minute (RPM) for 1 h/day, 5 days/week. Cell proliferation was measured using total protein quantification, and osteogenic activity was measured by alkaline phosphatase (ALP) activity, calcium deposition, and collagen production on days 7, 14, and 21 of culture. Results of DPCs morphology in the 30 RPM group were more clustered and formed interconnections between cells. Results of DPC proliferation and collagen production showed no significant differences between the experiment groups. The ALP activity on day 7 and 14, and calcium deposition on day 21 of the 30 RPM group were significantly higher than the control groups. Thus 30 RPM is likely an effective frequency for increasing calcium deposition. This study uses strategies in Tissue Engineering followed the research topic about an application of human cells to stimulate oral and maxillofacial hard tissue regeneration. In the future, the mineralization of DPCs could be enhanced by using an incubating rocking shaker at 30 RPM in the lab to create a cell sheet. The mineralized cell sheet could then be implanted into the patient for bone repair of orofacial defects.